Agro-physiological traits as biological factors to optimize organic and inorganic amendments for date palm cultivation - Mohamed Anli; Abderrahim Alahyane; Mohamed Ait Babram; Abderrahim Boutasknit; Cherkaoui El Modafar; Abdelilah Meddich (International Journal of Applied and Experimental Biology)
The date palm (Phoenix dactylifera L.) is the most important fruit crop in the oasis ecosystems due to its different ecological and socio-economic roles. However, this crop is confronted with environmental stresses such as soil poverty in organic and mineral matter. This research aimed at how local compost and/or phosphate sludge (PS) can affect the agro-physiological parameters of date palm over time in a greenhouse environment. The results showed that the factor time (period) presented a positive effect in the improvement of the physiology (stomatal conductance and chlorophyll fluorescence) and the growth (number of leaves, shoot height, and leaf area) of date palm seedlings treated with compost and PS + Compost in the periods P4-P9 and P8-P9, respectively, compared to the control. In addition, this study revealed the effectiveness of compost alone or combined with PS to boost the growth performances and physiology of date palm seedlings from the second month of the experiment with an apparent difference after four months of compost and PS application. It is clear from this study that the application of compost and its combination with PS could be a biological tool to improve date palm development under poor soil.